Economic Liberalization Impact, Fiscal Conditions, and Tax Ratio to Welfare - Johadi, Johadi; Pribadi, Kresno Sarosa; Daerobi, Ahmad; Mulyani, Nunung Sri (Universitas Negeri Semarang, 2019)
Global economy has currently integrated and has been interdependent between the developing and developed countries. The improved integration and interdependence level is expected to improve citizens’ welfare. This study aims at testing the correlation between fiscal and trade policies and welfare in ASEAN countries + 3 countries (Singapore, Malaysia, Indonesia, Thailand, Philippines, Brunei Darussalam, Cambodia, Vietnam, Myanmar, Laos + Japan, China, and Korea). It used the secondary data from World Bank, Asian Development Bank (ADB) and Economist Intelligence Unit from 1990 to 2015. The analysis uses the POLS-ECM (Panel Ordinary Least Square-Eagle Granger Error Correction Model). The results of analysis show that economic growth, infrastructure capital expenditure, economic openness, and tax ratio had a significant effect on welfare ASEAN + 3 countries